1980
DOI: 10.1021/bi00563a012
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic mechanism of Escherichia coli alkaline phosphatase: resolution of three variants of the acyl-enzyme mechanism

Abstract: Three variants of the classical acyl-enzyme mechanism were compared theoretically with respect to the predicted transient kinetics of substrate hydrolysis by Escherichia coli alkaline phosphatase. In all three, acyl-enzyme hydrolysis was assumed to exist initially primarily as a noncovalent complex with the acid product, inorganic phosphate. In one mechanism, the pre-steady-state rate-controlling step was assumed to be the dissociation of acid product from its initial complex with enzyme. In the other two, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 33 publications
6
25
0
1
Order By: Relevance
“…On the other hand, for alkyl phosphate substrates the computed values point to the nucleophilic attack of the serine alkoxide to phosphorus ( k 2 ) as the rate-determining step. While for aryl phosphates the rate-determining step corresponds to product release ( k 4 in Scheme ) at pH > 7.5 and to hydrolysis of the phosphoserine ( k 3 ) at pH < 7.5, phosphorylation of the enzyme ( k 2 ) has been hinted as rate-limiting for alkyl phosphates . Hence, the present computational results are in accordance with the mechanistic interpretations arising from experimental observations.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…On the other hand, for alkyl phosphate substrates the computed values point to the nucleophilic attack of the serine alkoxide to phosphorus ( k 2 ) as the rate-determining step. While for aryl phosphates the rate-determining step corresponds to product release ( k 4 in Scheme ) at pH > 7.5 and to hydrolysis of the phosphoserine ( k 3 ) at pH < 7.5, phosphorylation of the enzyme ( k 2 ) has been hinted as rate-limiting for alkyl phosphates . Hence, the present computational results are in accordance with the mechanistic interpretations arising from experimental observations.…”
Section: Resultssupporting
confidence: 87%
“…In regard to the second chemical step ( k 3 ), the presence of a more basic alkyl oxide anion would help the proton transfer from the Zn 1 -coordinated water molecule to generate the nucleophilic hydroxide (step 3 in Scheme ), assisting the hydrolysis of the phosphoserine intermediate; on the other hand, formation of the hydroxide ion would be less facile in the presence of an aryl substrate (step 3 in Scheme ). Therefore, the second energy barrier becomes the highest for aryl phosphates, with the enzymatic rate-determining step being highly influenced by the pH of the medium (at pH < 7.5, k 3 is rate-limiting; at pH > 7.5, k 4 is rate-limiting). A p K a of 8.0 has been suggested for the zinc-coordinated water …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both binding and release of neutral substrates and products were fast. A slow release of a charged product (PO 4 Ϫ , "sticky acid") from the noncovalent complex also occurs in alkaline phosphatase (19), although in this study no evidence was found that release was preceded by an enzyme isomerization, as was suggested by others (20).…”
Section: Discussionsupporting
confidence: 42%
“…The dimeric AP molecule has a molecular mass of 95 kDa with two tightly bound zinc ions, and one magnesium ion in each of the active centers of the two identical subunits. Its kinetic properties have been well characterized and it has been established that phosphate dissociation from the enzyme is the rate-limiting step in catalysis at alkaline pH (Reid and Wilson, 1971 ;Hull et al, 1976;Bloch and Gorby, 1980;Gettins and Coleman, 1984;Gettins et al, 1985).…”
mentioning
confidence: 99%